Resuscitative endovascular balloon oclusion of the aorta (REBOA) in non-traumatic cardiac arrest in a pig-model: Influence on Return of spontaneous circulation (ROSC) with short-term survival, gas exchange and hemodynamics - Randi Katrin Manegold; Philip Scheene; Andreas Wissmann; Fadi Al Rashid; Birte von der Beck; Nikolaus Pizanis; Clemens Kill; Joachim Risse (PLoS ONE, 2025)
Background Survival of out-of-hospital cardiac arrest (OHCA) remains poor even when bystander cardiopulmonary resuscitation (CPR) with chest compression is initiated. Chest compressions provide only reduced cardiac output with limited perfusion of heart and brain and therfore may not avoid both death or poor neurological outcome in prolonged CPR. We investigated the impact of resuscitative endovascular balloon occlusion of the aorta (REBOA) on hemodynamics, gas exchange and return of spontanous circulation (ROSC) with short-term survival during mechanical CPR (mCPR) with chest compression synchronized-ventilation (CCSV) in an atraumatic pig model. Methods The study was performed on 20 pigs under general anaesthesia. REBOA catheter was placed in the thoracic aorta at the level of diaphragm beforecardiac arrest (CA) with ventricular fibrillation (VF) was induced. After 3 minutes of CA mCPR was started, CCSV was initiated at t = 5 min. Radomization to REBOA or control group, at t = 7 min inflation of REBOA ballon. CPR was continued until t = 18 min including defibrillation and intravenous epinephrine. Primary endpoint was ROSC with short-term survival, secondary endpoints mean arterial pressures (MAP) and arterial bloodgas analyses. Results ROSC was observed in n = 5 (REBOA) versus n = 1 (control) out of 10 animals, p = 0.141. All these animals remained stable for over an hour and thus also met the criteria for short-term survival. In the REBOA group, MAP was significantly increased following blockage of the ballon. Arterial blood gas analyses (ABG) showed a trend to higher PaO2 (REBOA 375 ± 147 mmHg vs control 277 ± 129 p = 0,220), higher pH-value (REBOA 7,37 ± 0,06 vs control 7,24 ± 0,12 p = 0,052) and less increased PaCO2 (REBOA 38 ± 7 mmHg vs control 59 ± 21 mmHg p = 0,056) at t = 14 min. Conclusion In our animal resuscitation model of non-traumatic CA, REBOA showed a significant increase in MAP and a favourable influence on gasexchange, associated with a trend towards higher ROSC rates and short-term survival. It remains to be seen whether these effects can be replicated in larger experimental and clinical studies.